+0  
 
0
330
1
avatar

Create an equation that has the three solutions x=2,4, and 5.

Guest Aug 12, 2017

Best Answer 

 #1
avatar+1860 
+1

To find an equation that has the three solutions of 2, 4, and 5, first set each solution equal to x.

 

\(x=2\)

 

\(x=4\)

 

\(x=5\)

 

Next, figure out what number goes with each of the three solutions that makes x equal to zero on the right side.  For x=2, the number will be -2; for x=4, the number is -4; for x=5, the number will be -5. What you do on the right side, you do to the left side as well.

 

\(x=2\)

 

\(x-2=2-2\)

 

\(x-2=0\)

 

\(x=4\)

 

\(x-4=4-4\)

 

\(x-4=0\)

 

\(x=5\)

 

\(x-5=5-5\)

 

\(x-5=0\)

 

Next, combine all three equations using the zero product.

 

\((x-2)\times(x-4)\times(x-5)=0\)

 

Next, expand the left side.

 

\((x-2)\times(x-4)\times(x-5)=0\)

 

\(({x}^{2}-4x-2x+8)\times(x-5)=0\)

 

\(({x}^{2}-6x+8)\times(x-5)=0\)

 

\({x}^{3}-5{x}^{2}-6{x}^{2}+30x+8x-40=0\)

 

\({x}^{3}-11{x}^{2}+38x-40=0\)

 

Next, replace 0 on the right side with y and then switch the equation around so that the y is on the left side.

 

\({x}^{3}-11{x}^{2}+38x-40=y\)

 

\(y={x}^{3}-11{x}^{2}+38x-40\)

gibsonj338  Aug 12, 2017
edited by gibsonj338  Aug 12, 2017
 #1
avatar+1860 
+1
Best Answer

To find an equation that has the three solutions of 2, 4, and 5, first set each solution equal to x.

 

\(x=2\)

 

\(x=4\)

 

\(x=5\)

 

Next, figure out what number goes with each of the three solutions that makes x equal to zero on the right side.  For x=2, the number will be -2; for x=4, the number is -4; for x=5, the number will be -5. What you do on the right side, you do to the left side as well.

 

\(x=2\)

 

\(x-2=2-2\)

 

\(x-2=0\)

 

\(x=4\)

 

\(x-4=4-4\)

 

\(x-4=0\)

 

\(x=5\)

 

\(x-5=5-5\)

 

\(x-5=0\)

 

Next, combine all three equations using the zero product.

 

\((x-2)\times(x-4)\times(x-5)=0\)

 

Next, expand the left side.

 

\((x-2)\times(x-4)\times(x-5)=0\)

 

\(({x}^{2}-4x-2x+8)\times(x-5)=0\)

 

\(({x}^{2}-6x+8)\times(x-5)=0\)

 

\({x}^{3}-5{x}^{2}-6{x}^{2}+30x+8x-40=0\)

 

\({x}^{3}-11{x}^{2}+38x-40=0\)

 

Next, replace 0 on the right side with y and then switch the equation around so that the y is on the left side.

 

\({x}^{3}-11{x}^{2}+38x-40=y\)

 

\(y={x}^{3}-11{x}^{2}+38x-40\)

gibsonj338  Aug 12, 2017
edited by gibsonj338  Aug 12, 2017

10 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.